Patient selection in congenital pyriform aperture stenosis repair – 14 year experience and systematic review of literature. Issue 2 (February 2015) - Gonik, Nathan J.; Cheng, Jeffrey; Lesser, Martin; Shikowitz, Mark J.; Smith, Lee P.
Abstract Purpose Congenital nasal pyriform aperture stenosis (CNPAS) is a rare cause of respiratory distress in neonates that may necessitate early surgical intervention. Restenosis and granulation are postoperative concerns that may prompt a return to the operating room. Reoperation places children at increased risk of perioperative complications and prolonged hospital stays. We are presenting a review of our institutional experience of 16 patients treated for CNPAS over a 14 year period and a systematic review with pooled data analysis to determine the effect of craniofacial and neurologic anomalies on surgical success. Methods Retrospective chart review of all cases of CNPAS treated at our tertiary children's hospital between 1999 and 2013. Systematic review of English language literature was conducted adhering to the PRISMA statement to determine the effect of neurologic anomalies and craniofacial dysmorphism (CFD) on surgical failure for CNPAS treatment. Univariate and exact multiple logistic regression were used for analysis of an individual patient data analysis. Results 10 patients had surgery and 6 were treated medically. Average pyriform apertures were 5.71 ± 1.72 mm for the surgical group and 4.83 ± 1.26 mm for the medical group (p = 0.38). 31% had neurological impairments. 31% had craniofacial dysmorphisms (CFD). 2 patients developed restenosis and 1 required tracheotomy. Both of these patients had other CFDs. Literature review captured 63 surgical patients and 9 failures in 6 series of CNPAS. 4.6% of patients without CFD and 36.8% of patients with CFD required surgical revision (p = 0.023, OR13.8). Conclusion When repairing CNPAS, co-morbidities must be considered. Impaired respiration, central neurologic deficits and extensive craniofacial anomalies may require additional surgeries or an alternative approach.